O32 Use of In-Situ simulation to tackle latent threats in a major haemorrhage protocol – difficulties and determination. (3rd November 2019) - Woodruff, Jenny; Wadia, Toranj; Korb, Cecilia; Gaspar, Mihaela; Lane, Mary; Burmester, Margarita
Abstract : Introduction: Major Haemorrhage carries a high mortality of 32% 1 and requires a co-ordinated response from bloodbank, clinical areas and porters. In-situ simulation can reveal latent threats which are not shown by Patient Safety Incident reporting. 2 Repeated simulations allow iterative Quality Improvement (QI) to mitigate latent threats. In this tertiary hospital specialising in adult and paediatric cardiac surgery we experience on average 17 Major Haemorrhage cases a year. We report our experiences of SPRinT (Simulated interPRofessional Team Training) in-situ simulations of Major Haemorrhage between 2012 and 2018. We discuss the latent threats identified and arising QI projects. Methods: Repeated SPRinT courses were planned cross-departmentally on the ward and in bloodbank to deliver simulated major haemorrhage events. The 'Plan-Do-Study-Act' tool was applied to the Massive Blood Loss (MBL) guideline to identify latent threats and deliver QI. Observer checklists measured compliance with any new changes. Systems errors responsible for poor outcomes were identified and staff trained. This process was repeated in multiple PDSA cycles with the aim to reduce latent threats to zero. Time to start transfusion of both the first unit of blood, and subsequent cross-matched blood, were monitored. Participants' confidence was monitored with questionnaires. Observer checklists were analysed in cross-departmental meetings looking for solutions. QI aims were categorised into efficiency, patient safety and reducing wastage. Results: A total of 9 SPRinT courses and 8 PDSA cycles were completed between 2012 and 2018, with 74 participants. Feedback forms suggest realism of the scenario's environment and stress level were 82% (IQR 70–90%) and 80% (IQR 65–90%) respectively. Latent threats were identified resulting in 7 significant QI projects (figure 1 ). Time for emergency blood administration improved from 6.15 mins to 2.0 mins (reduction of 2/3rds). Discussion/Conclusion: Over 3 years of simulation-based PDSA we have overhauled our Major Blood Loss Protocol (figure 1 ), resulting in increased participant confidence and reduced time to initial blood transfusion. QI projects have included tackling systems issues such as a lack of overnight access to an outlying site, providing improved resources eg a cordless phone for Bloodbank. The iterative simulation process was used to improve our Major Blood Loss Protocol by combating latent threats, and for staff training. The time to resolve major QI issues was greatest for estates issues (4 years) followed by additional resources (1 year) and training (6 months) (table 1 ). We have shown that with targeted in-situ simulations, and determination, major improvements are possible in cross departmental protocols. References: Green, et al: Transfusion Medicine 2017. Green L., Tan J., Grist C., Kaur M, MacCallum P. (2017). Aetiology and outcome of massive transfusion in two large London teaching hospitals over a 3-year period (2012–2014). Transfusion Med, 27: 342–347. doi:10.1111/tme.12434 Knight, et al. Mitigating latent threats identified through an embedded in situ simulation program and their comparison to patient safety incidents: a retrospective review. Front. Pediatr, 01 February 2018.